Analysis of Tapered Microstrip Patch Antenna with Slot Integration at 28 GHz for Satellite Communications - J, Josiah Samuel Raj; G, Anitha (2024 9th International Conference on Communication and Electronics Systems (ICCES), 2024)
An innovative antenna design that has been specifically engineered for 28 GHz communication systems is presented in this study. This design was developed to fulfill the demand for high-performance, wideband antennas that are suitable for use in radar and satellite applications specifically. A rectangular microstrip patch with tapered corners and a slot that is strategically positioned is included in the proposed antenna design. This patch is fabricated on a FR4 substrate that is 1.6 mm in height and has a dielectric constant of 4.4. Inset feeding and partial ground plane techniques are utilized in order to optimize the design, using Ansys HFSS software. The antenna exhibits remarkable performance characteristics, including a return loss of −69.5042 dB at a frequency of 27.29 GHz, a Voltage Standing Wave Ratio (VSWR) of 1.0007 at the same frequency, and an impedance matching of 49.98 ohms. In addition, it achieves a notable gain of 5.2 dB and possesses an extensive bandwidth of 5.26 GHz, giving it an advantage over conventional designs in terms of versatility and efficiency. In this study, the effectiveness of the proposed antenna architecture is demonstrated, and the potential of the architecture to improve communication systems of the next generation that operate at millimetre-wave (mmW) frequencies is addressed.